Epoxidized natural rubber–alumina nanoparticle composites: Optimization of mixer parameters via response surface methodology - Mohamad, Noraiham; Muchtar, Andanastuti; Ghazali, Mariyam Jameelah; Hj Mohd, Dahlan; Azhari, Che Husna (John Wiley & Sons, 2010)
Epoxidized natural rubber–alumina nanoparticle composites were prepared by melt compounding with an internal mixer for a constant filler loading of 10 phr. Mixer parameters such as the mixing temperature, mixing time, and rotor speed were screened and optimized with response surface methodology to maximize the impact strength. The parameters were selected as three independent variables and the impact strength (J/m) was selected as the response in a screening factor study. The mixing temperature and its interaction terms were identified as insignificant factors with a P value greater than 0.0500. The optimum calculated values of the tested variables (rotor speed and mixing time) for the maximum impact strength were found to be a rotor speed of 60 rpm and a mixing time of 6 min with a predicted impact strength of 208.88 J/m. These predicted optimum parameters were tested in real experiments. The final impact strength was found to be close to the predicted value of 215.84 J/m, with only a 3.33% deviation.